실험실 규모 칼럼에서의 팔라디움-인디움-알루미나 촉매를 이용한 지하수 내 질산성질소 제거 - 김홍현; 정상조 (한국수처리학회지, 26(5), 2018)
In order to develop optimal operation conditions for nitrate removal in a continuous flow system which has a 5% palladium-0.65% indium on alumina catalyst, the effects of initial concentration of nitrate, flow rate, and temperature were evaluated. First, the rates of nitrate removal decreased from 100% to 69% when the initial concentration of nitrate increased from 150 mg/L to 300 mg/L. Second, as the flow rate of nitrate decreased from 2 ml/min to 0.5 ml/min, the nitrate removal efficiency increased from 40% to 80% when the initial concentration of nitrate was 300 mg/L. Third, when increasing the column temperature from 0℃ to 80℃, the removal rate of nitrate increased from 20% to 96%. In addition, the production of N2, NO2-, NH4+, and changes of pH due to the reduction of nitrate were analyzed. In order to reactivate the catalyst, treatment using 56 mM NaOCl solution was more efficient than that using 56 mM H2O2 or 1 M HCOOH. The characteristics of the various parameters derived from the laboratory scale column experiments are thought to be of great help in the operation of nitrate removal system in the field. KCI Citation Count: 0